Mathematical-cartographic modeling of the housing sector in the GIS environment - Vladimir Sergeevich Tikunov; Alexey Vladimirovich Popkov (Наука. Инновации. Технологии)
Among the fundamental objectives of the housing construction, the most significant are the task of active development of territories for different types of housing construction and the establishment in each municipality housing stock of social usage in proportions corresponding to the needs of the staff of the municipality. Application of modern scientific and practical methodologies in the sphere of housing spatial planning allows to study the existing problems more effectively and precisely plan the ways of their solution, as well as to predict the situation in the foreseeable future. According to the authors, methods of mathematical-cartographic modeling in insufficiently utilized for planning and housing in particular. For the first time this classic method is used for simulation of the housing sector of the municipal district and are copyrighted card-schemes reflecting the indicators based on the example of municipal district Ramenki of Moscow. In mathematical-cartographic modelling always problem is quite acute automate calculations. At the very large number of nodes a regular lattice, which are of a formula, the problem of repeated calculation values according to the same formula that requires a large amount of computing re-sources. Mathematical-cartographic support using the «gravity» of models allows to predict development of the situation and helps in decision making in the planning of territories, to predict the possible problems and selection of the correct ways of their solution.